Dense + Green Cities. Architecture as Urban Ecosystem. - Schröpfer, Thomas (Birkhäuser, 2020)
The emergent understanding of the building and the city as ecological systems immediately raises the question of their interaction. In which ways does a "green building" contribute to the ecology of its surroundings? And how can ecologically designed urban districts, with their green and blue networks, link up with the elements and technologies of building design? These are questions of concept, of planning, of design and not least of experience. All these dimensions of "green building" are investigated in this book with substantial essays and benchmark case studies, in a collaboration of a research team with internationally renowned architects, urbanists and landscape designers – in an effort to understand and evaluate some of the most recent and innovative Dense+Green Cities in Asia, the Americas and Europe.
Keywords: Stadtplanung; Bebauungsdichte; Nachverdichtung; Stadtgrün; Ökosystem; Stadtökologie; Green Building; Wirkung; Stadtraum; Stadtgrün; Stadtpark; Grünraum; Großstadt; Fallstudie; Beispielsammlung